2003
DOI: 10.1097/01.ju.0000091804.20183.81
|View full text |Cite
|
Sign up to set email alerts
|

5α-Reductase Type 1 Immunostaining is Enhanced in Some Prostate Cancers Compared With Benign Prostatic Hyperplasia Epithelium

Abstract: The presence of increased 5alphaR1 in some prostatic malignancies suggests that it is worthwhile to investigate the use of a dual 5alphaR inhibitor to prevent or treat early stage prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 18 publications
3
36
0
1
Order By: Relevance
“…Thigpen et al (24) showed that steroid 5a-reductase isozyme II is the predominant isoform in prostate tissue. Recent evidence supports increased isozyme I expression in prostate cancer (25) and recurrent prostate cancer (26). Catalytic activity at 50% maximal rate requires higher substrate concentration (testosterone) for steroid 5a-reductase isozyme I than isozyme II (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thigpen et al (24) showed that steroid 5a-reductase isozyme II is the predominant isoform in prostate tissue. Recent evidence supports increased isozyme I expression in prostate cancer (25) and recurrent prostate cancer (26). Catalytic activity at 50% maximal rate requires higher substrate concentration (testosterone) for steroid 5a-reductase isozyme I than isozyme II (27).…”
Section: Discussionmentioning
confidence: 99%
“…Previously published reports 5,22 have demonstrated decreased expression of 5 ␣-reductase type II in prostate cancer specimens by microarray, reverse transcriptase-PCR analysis, 5 and immunostaining. 22 Thomas et al 23 demonstrated high immunoreactivity for 5 ␣-reductase Type I in 28% of prostate tumor epithelia specimens. Differences in the expression of 5 ␣-reductase isoenzymes in our samples also may reflect the primary nature of the model used.…”
Section: 12mentioning
confidence: 99%
“…The cancer specimen showed 5a-R1 staining in the epithelium in 81% (high intensity in 28%) and in the stroma in 92% (high intensity in 21%). Thomas et al 8 suggested that 5a-R1 is of greater importance in promoting and maintaining prostate cancer as compared to 5a-R2. In an extension of this work, Thomas et al 9 found that 5a-R1 moderate plus high intensity immunostaining was augmented from 4.8% of total epithelial area in BPH to 17% in primary over 38% in recurrent, and 55.8% in metastases of prostate cancer, whereas 5a-R2 showed varying responses.…”
Section: Methodsmentioning
confidence: 99%
“…Both 5a-R isoforms are increased in 'androgen-independent' cancer which may reflect an adaptive or selective mechanism to amplify any remaining androgen signal. 8 The application of inhibitors of the 5a-R1 and 5a-R2 isoforms in cultures of primary prostate cancer decreased the cell proliferation dose-dependently through auto-or paracrine mechanisms. 53 When patients are treated with Dutasteride 6-10 weeks before radical prostatectomy the intraprostatic DHT 5a-Reductase inhibitor treatment J Dörsam and J Altwein was reduced by 97% and apoptosis was augmented possibly indicating tumor regression.…”
Section: Chemoprevention Of Prostate Cancermentioning
confidence: 99%